Quantity or quality?: Assessing the role of household structure and parent-child relationship in juvenile delinquency - Jacobsen, Shannon K. (Deviant behavior, 2022)
Research investigating the risk factors for delinquency has found that single-parent households are more criminogenic than two-parent households. Using data (N = 4,626) from the National Longitudinal Study of Adolescent to Adult Health, this study expands on prior research by considering various types of households and parent-child relationship, along with three categories of delinquency: status offenses, property crimes, and violent crimes. Contrary to previous research, we find that juveniles living in single-parent households are significantly less likely to engage in all three types of delinquency than those from intact and stepparent households. Further, while an increased quantity of parents in the household does not lessen engagement in delinquency, the quality of the parent-child relationship does, as those who have stronger relationships with their parents are at lower risk of delinquent behavior. Our study highlights the importance of distinguishing between different types of delinquency and household structures, as well as how such classifications may influence research findings in this area.